2020
DOI: 10.2147/ppa.s230286
|View full text |Cite
|
Sign up to set email alerts
|

<p>Modeling Lay People’s Ethical Attitudes to Organ Donation: A Q-Methodology Study</p>

Abstract: Background: Organ donation is commonly evaluated by biomedical ethicists based largely on principlism with autonomy at the top of the "moral mountain." Lay people may differ in the way they invoke and balance the various ethical interests. We explored lay people's ethical attitudes to organ donation. Methods: Respondents (n=196) ranked 42 opinion-statements on organ donation according to a 9-category symmetrical distribution. Statements' scores were analyzed by averaginganalysis and Q-methodology. Results: Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
3
1
0
Order By: Relevance
“…On the other hand, patient's preference-related determinants were strongly embraced in only 3 models and strongly discounted in 5. The results are in general agreement with a related US study that used a different design and mainly recruited white educated women 6 and with studies on laypeople's attitude to organ donation 29 and placebos, 28 showing predominance of consequences over autonomy. The results are also consistent with the current preference thesis that takes into account only experiential interests and believes that interests do not survive loss of mental capacity, 7,8 they and provide some empirical evidence against the prospective/extended autonomy concept and substituted judgment standard, where surrogate decision making is based on stated or predicted wishes of the patient.…”
Section: Predominance Of Patient's Healthsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, patient's preference-related determinants were strongly embraced in only 3 models and strongly discounted in 5. The results are in general agreement with a related US study that used a different design and mainly recruited white educated women 6 and with studies on laypeople's attitude to organ donation 29 and placebos, 28 showing predominance of consequences over autonomy. The results are also consistent with the current preference thesis that takes into account only experiential interests and believes that interests do not survive loss of mental capacity, 7,8 they and provide some empirical evidence against the prospective/extended autonomy concept and substituted judgment standard, where surrogate decision making is based on stated or predicted wishes of the patient.…”
Section: Predominance Of Patient's Healthsupporting
confidence: 89%
“…Family-centric determinants and surrogate's interestrelated determinants were strongly embraced in 8 EA models compared to 1 ME model. This suggests that EA men may be more family focused than ME men and is consistent with the prevalence of familism in East Asia, 16,17,36 studies showing a stronger familism orientation in Christian/Philippines-educated than Muslim/ Saudi Arabia-educated respondents in relation to organ donation, 29 and studies showing culture dependency of end-of-life preferences. 21,22,37 However, although Q-methodology identified relatively familism-influenced models in all EA viewpoints, there were also a relatively familism-influenced model in the ME S-viewpoint and a relatively family burden-influenced model in the ME Pviewpoint.…”
Section: Comparing Middle Eastern and East Asian Mensupporting
confidence: 56%
“…Consistently, a previous study using simple rating and dichotomization showed that 78% of surrogates (mostly white educated US women) focused more on patient's well-being than patient's preferences [6]. A predominance of consequentialist attitude over autonomy-based attitude was also observed in lay people approach to medical use of placebos [34] and organ donation, [35] providing support to the concept that "good" may be more fundamental than "right" and to the importance of "harm/care" as one of the psychological foundations of morality [36].…”
Section: Importance Of Patient's Healthsupporting
confidence: 70%
“…Q-methodology is a quali-quantitative methodology that originated in the field of psychology (Brown, 1980) but is now used in a wide array of fields to understand the range of stakeholder perceptions in reference to contested issues [e.g., education (Rodl et al, 2020), medicine (Hammami et al, 2020), and environment (Moros et al, 2020)]. Q-methodology combines statistical analysis in the form of a data-reduction technique applied to pseudo-ranking data with the analysis of qualitative data obtained during the ranking exercise to reveal core perceptions.…”
Section: Q-methodologymentioning
confidence: 99%